2011
DOI: 10.1016/j.ejcts.2010.12.043
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of paravertebral block using a catheter technique for postoperative analgesia in thoracoscopic surgery: a randomized trial☆

Abstract: The analgesic regimen combining PVB and NSAID provided an excellent level of pain control. Thoracoscopy assisted positioning of the paravertebral catheter is simple and effective, and allows direct visualization of correct delivery of local anesthetic. It represents a valuable addition to any VATS procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 21 publications
1
30
0
4
Order By: Relevance
“…After confirmation that there was no dissemination, but before initiation of the thoracotomy, the paravertebral catheter was inserted in a manner that has been previously described [1114], as follows: The upper edge of the spinous process of the T5 vertebral body was palpated through the skin. With the assistance of forceps inserted through the same camera port, the paravertebral space was visualized under thoracoscopy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After confirmation that there was no dissemination, but before initiation of the thoracotomy, the paravertebral catheter was inserted in a manner that has been previously described [1114], as follows: The upper edge of the spinous process of the T5 vertebral body was palpated through the skin. With the assistance of forceps inserted through the same camera port, the paravertebral space was visualized under thoracoscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Our preliminary trials of thoracic PVB led us to suspect a strong correlation between a number of reported insertion methods [3, 4, 610] and substantial leak of local anesthetic into the pleural space, which results in less effective postoperative pain control. However, some authors have described the effectiveness of intraoperative percutaneous catheter placement during video-assisted thoracoscopic surgery (VATS) [11, 12]. This insertion method offers better pain control, as the extra-pleural space is closed above the catheter tip, allowing no leakage into the pleural space and facilitating easy coverage of more than one intercostal space.…”
Section: Introductionmentioning
confidence: 99%
“…Paravertebral blocks (PVBs) are used often in the management of pain following thoracotomy, video-assisted thoracoscopic surgery, and mastectomy. [41][42][43] Much like epidural analgesia, their drawbacks include increased time for placement, but PVBs are not associated with a risk of paralysis or urinary retention. Studies have consistently illustrated the Volume 134, Number 4S-2 • Autologous and Implant-Based Breast Reconstruction 123S benefit of PVBs following mastectomy including decreased nausea and faster return to work.…”
Section: Nontraditionalmentioning
confidence: 99%
“…After the surgical incision, the first pain sensation is mostly nociceptive; commonly, the use of NSAIDs is theoretical. One RCT of a small number of TS wedge resections (n=40) reported improved pain relief and reduced morphine consumption when PVB with ropivacaine was compared with IV NSAIDs using paracetamol plus metamizol (18). The authors concluded that the analgesic regimen combining PVB and NSAID provides an excellent level of pain control (19).…”
Section: Multimodal Analgesic Regimen Non-opioidsmentioning
confidence: 99%